The practice of using chill vents in construction injection molding forms - V. I. Chechukha; M. A. Sadokha; S. V. Kareniuhin (Литьë и металлургия, 2024)
Options for improving the quality of castings during injection molding are considered. The variants of the design and placement of the chill vents in the mold are presented. The practical experience of using chill vents in order to improve the ventilation system of the mold to ensure a reduction in the defect of the gas sink molds and porosity is described.